A implementação da política de Educação de Jovens e Adultos (EJA) em uma escola municipal de Vitória/ES : apostas e tensionamentos - Romanio, Marcel Bittencourt (2011)
This study aimed to monitor the effects of the implementation process of the municipal policy for Youth and Adults (EJA) in a public school in the city of Vitória/ES. To analyze the data produced in the survey we used two vectors, namely the establishment of educational practices that weave the Youth and Adult Education in Brazil and the processes that permeated the implementation of adult education policy, formulated from 2005 by the Municipal Education Victoria / Holy Spirit (SEME/ES). The survey encompassed institutional experience and interviews with teachers who work in adult education in a school sport in the municipal Vitória/ES, interviews with team policy coordination EJA that acts at the central (SEME) and participation in meetings of the training teachers. The paper highlights some moves that were experienced by teachers as tensions that permeated the process of implementing a policy of municipal adult education school in the survey, such as the arrival of the proposal to the school, the tensions, dilemmas and achievements interfering in the politics of adult education, training and management processes of teaching, the process of juvenilization EJA, among others. The process of implementing a policy of adult education in Vitória/ES has been performing in line with propositions woven into the field of adult education nationwide. In the survey we have seen from the implementation process caused destabilization experienced in institutionalized practices in school and also the discussions conducted with teachers often diverted the proposal submitted by the coordination team of the EJA SEME/ES